Research on High Effi ciency Computing Technology Based on COTS Products - Yue ZHANG; Yubing ZHANG; Tianqi MA; Bin LI; Yenan SHI (天地一体化信息网络)
Aiming at the problem of space environment adaptability of COTS products,the fault tolerance reinforcement of space computer was carried out through crosss layer collaborative software fault tolerant technology.The space computer based on COTS product was designed and developed.Through carrying the last stage rocket,the on orbit technical test was carried out for six months.The test results show that the proposed method can improve the space environment adaptability of COTS products,it has guiding signifi cance to promote the aerospace application of commercial shelf products.